2008
DOI: 10.1016/j.tcs.2008.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Measuring teachability using variants of the teaching dimension

Abstract: In a typical algorithmic learning model, a learner has to identify a target object from partial information. Conversely, in a teaching model a teacher has to give information that allows the learners to identify a target object. We devise two variants of the classical teaching model for Boolean concept classes, based on the teaching dimension, and describe them by teaching-dimensionlike combinatorial parameters. In the first model, the learners choose consistent hypotheses with least complexity. We show that 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 29 publications
0
38
0
1
Order By: Relevance
“…The largest number of examples required at any stage is the recursive teaching dimension (RTD) of C. The RTD significantly improves on bounds for previous teaching models. It lower-bounds not only the complexity of the "classical" teaching model [6,19] but also the complexity of iterated optimal teaching [2], which is often significantly below the classical teaching dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The largest number of examples required at any stage is the recursive teaching dimension (RTD) of C. The RTD significantly improves on bounds for previous teaching models. It lower-bounds not only the complexity of the "classical" teaching model [6,19] but also the complexity of iterated optimal teaching [2], which is often significantly below the classical teaching dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent direction assumes a helpful and powerful teacher who provides a minimal set of examples necessary for learning a concept, so the learner can eliminate competing concepts based on the size of the teaching set [3,28]. Naturally, the strange behavior of the learner on the contradictory concept also vanishes in this model (and in fact, this concept has a teaching set of size O(1)), but only under the troublesome assumption that the learner "knows" the optimal size of teaching sets-troublesome because Servedio [25] showed that the optimal size of teaching sets (in the traditional sense) is NP-hard to compute, so it is doubtful that these more sophisticated notions of teaching dimension could be computed easily.…”
Section: Existing Models Of Teachingmentioning
confidence: 99%
“…One such model (see Balbach [7,8]) assumes the learner picks hypotheses that are not only consistent but of minimal complexity. This model is inspired by the Occam's razor principle.…”
Section: Further Directionsmentioning
confidence: 99%
“…Another variant devised by Balbach [8] assumes that the learners know the teaching dimensions of all concepts in the class and choose their hypotheses only from the consistent ones with a teaching dimension at least as large as the sample given by the teacher. In other words, they assume the teacher does not give more examples than necessary for the concept to be taught.…”
Section: Further Directionsmentioning
confidence: 99%
See 1 more Smart Citation